Asymmetric Effects of Exchange Rate Changes and the J‐curve: New Evidence from 61 Malaysia–Thailand Industries. Issue 4 (7th December 2016) - Bahmani‐Oskooee, Mohsen; Aftab, Muhammad
Abstract: Research on the impact of currency depreciation on the trade balance is now moving in a new direction by incorporating nonlinear dynamic adjustment of the exchange rate and by using a nonlinear approach to error‐correction modeling and cointegration. Using these advances, researchers find not only more evidence of the J‐curve effect, but also new evidence of asymmetric effects of exchange rate changes on the trade balance. We contribute to this line of research by using monthly trade flow data from 61 two‐digit industries that trade between Malaysia and Thailand, and show that not only does currency depreciation have favorable effects on the trade balance of more industries, but the long‐run effects are asymmetric in 26 out of 61 cases. In line with current literature, our nonlinear model performs much better than the linear model when industry level data are used.